Investigation of the extreme scenario hydrologic response of Marikina watershed considering historical and land use change using DEM-based hydrologic models - Billones, Benzene June T.; Martinez, Justin Joseph S.; Herrera, Eugene C. (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
Hydrologic modeling is important for understanding the responses of watersheds to environmental-related changes like land cover-and climate change (extreme droughts and rainfall) with limited amount of temporal and spatial hydrographic information. With a hydrologic model watershed management can be more efficiently implemented and can be a powerful tool for future ecological restorations. Investigating the watershed hydrologic response using actual data is ideal but these information are relatively hard to obtain that is why a DEM-based hydrologic model is used in this study in assessing the most critical sub-watershed of Laguna de Bay, Marikina sub-basin. Model Simulation was done using ArcSWAT (hydrological component of ArcGIS) by applying year 2003 Marikina data set (weather data, land use and soil cover). ArcSwat is a GIS ready model, and uses physical parameters as input, which is the best thing to use in assessing physical characteristics and responses like land-uses. Manual calibration was done by changing selected critical parameters and observing their contributory effect on the comparison between simulated and observed river discharges. Model calibration was achieved with an acceptable Nash-Sutcliffe value of 0.9, which is above the 0.4 acceptable value. Comparative analysis showed, that the mod el predicts the actual discharges within reasonable limits (quantity and timing). The most critical parameter that was found to decrease the surface flow significantly was SURLAG (representing surface lag parameters), with drops in simulated discharges equal to the drops with this parameter. Although R2 value decreases as the Nash-Sutcliff increases, and does not comply with the minimum requirement, it was not taken as a major consideration because the most critical points or the peaky ones must be close between the simulated and the actual, and if the R2 would be taken as one, it will result to a lower Nash-Sutcliffe value and to a poor curve fitting. Model validation was done next to calibration to ensure that the model can closely predict the actual discharges. Graphical approach was used to compare the results of the simulated with respect to the actual, and it shows acceptable curve fitting that reaches most of the peak discharges. After calibration and validation, model scenario simulations were done for three scenarios. The goal was to obtain the comparable effect or impact of land use change over an area. The parameters used were the calibrated ones obtained from model simulation and calibration of Marikina in year 2003 as described earlier. The three scenarios simulated were: 20 year projection after 2009; reforestation; and 1993 setting and data set. Simulations were done by manipulating or adjusting the land use coverages depending on the scenario, and by using 2009 rainfall data (Ondoy year) to observe critical fluctuations in discharges based on a 100-year rainfall. After the scenario simulations, it was found that the 20 years after 2009 scenario yields to more peaky discharges and lower base flows in between (flood-critical condition), reforestation corresponded to lower run-off discharges (conservation-critical condition) and 1993 set-up scenario results to a lower discharge as well (urban planning-critical condition). Thus, with this study, it can be concluded that indeed, land use change has a significant impact on the hydrology of watersheds and it is imperative that regulations on land developments be made.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Watersheds -- Mathematical models; Watersheds -- Philippines -- Marikina City; Watershed management